Mathyelo ya mavito ya swimawusa emugangeni wa ka Bungeni, eka xifundzatsongo xa Vhembe, exifundzenikulu xa Limpopo - Ntuli, Mafemani Freeman (My University, 2024)
The study examined the naming of spaza shop businesses in Bungeni area, Vhembe District, in the Limpopo Province. It is vital to name a spaza shop since it makes people know the feelings, traditions, culture, wishes, and value norms attached to a specific nation. In most instances, a name conveys to inhibitants or occupants in a site information of some kind portraying a narrative that impacts on their lives. In African society, people give names that carry a certain meaning which is related to their personal feelings, thoughts and believes. This research dissertation illustrates some glaring bad repurcations when spaza shop owners in Bungeni area neglect giving their spaza shops names that have positive influences to enhance an impactful contribution to the successes of their spaza shops. The study also outlined the reasons that culminate the owners of spaza shop businesses in Bungeni area, being influenced by their belief systems when naming their spaza shops. To conclude, the study indicated that numerous measures can be taken in making sure that spaza shop owners in Bungeni area, Vhembe District, Limpopo Province use names that bear positive influences thereby contributing to the success of their spaza shops
Naming of spaza shop businesses in Bungeni Area, Vhembe District, Limpopo Province
Thesis (M. A. (African Languages)) -- University of Limpopo, 2024
Keywords: Onomastics; Name; Bungeni and spaza; Names, Geographical -- Etimology; Onomastics